COHESIVENESS, SENSE OF ETHNICITY, AND STEREOTYPING IN THE GROUP COMMUNICATION OF BATAK STUDENTS IN BENGKULU UNIVERSITY - Ningrum, Dyaloka Puspita; Arrianie, Lely (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2020)
This article provides an overview of how group communication among Punguan Raja Sonang members, namely the association of students with Batak ethnic backgrounds from the clans of Gultom, Samosir, Sitinjak, Pakpahan and Harianja at the University of Bengkulu. Using a qualitative-descriptive approach with data collection methods by observation, in-depth interviews, and documentation, the results show that the members of Punguan Raja Sonang need the closest people that can help them get to know their fellow Bataks in a clan. The same background, area of origin, belief, and language make the members of Punguan Raja Sonang at the University of Bengkulu have cohesiveness or strength to remain in the clan group. In addition, their sense of Batakness is nurtured through group communication, although there are indications that some group members are colonized by certain Batak character stereotypes, which makes them participate in prejudging other group members who have anomalous characters. Above all, a close togetherness among them can create a high sense of solidarity both with older members and with young peers. To cite this article (7th APA style): Ningrum, D. P. & Arrianie, L. (2020). Cohesiveness, Sense of Ethnicity, and Stereotyping in the Group Communication of Batak Students in Bengkulu University. Journal Communication Spectrum, 10(1), 38-45. http://doi.org/10.36782/jcs.v10i1.1957